Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.2737/rm-gtr-229
|View full text |Cite
|
Sign up to set email alerts
|

Status and management of neotropical migratory birds

Abstract: This proceedings is the product of a National Training Workshop held at the Estes Park Center, Estes Park, Colorado, 21-25 September, 1992. Invited papers discuss all aspects of management, monitoring, and conservation of neotropical migratory birds on the breeding grounds. The proceedings is divided into seven sections that range from philosophical discussions to methods and solutions for managing migratory birds in concert with other wildlife.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 164 publications
0
10
0
Order By: Relevance
“…Initial concern over perceived population declines of some migratory songbirds led to the formation of the international bird conservation initiative called Partners in Flight (Finch and Stangel 1993). Partners in Flight (PIF) is a partnership of academic and private researchers, representatives of federal and state natural resource agencies, industry, and non-governmental natural resource or land management groups in the United States, Canada, and Latin America.…”
Section: Received 26 February 2001; Accepted 13 November 2001mentioning
confidence: 99%
“…Initial concern over perceived population declines of some migratory songbirds led to the formation of the international bird conservation initiative called Partners in Flight (Finch and Stangel 1993). Partners in Flight (PIF) is a partnership of academic and private researchers, representatives of federal and state natural resource agencies, industry, and non-governmental natural resource or land management groups in the United States, Canada, and Latin America.…”
Section: Received 26 February 2001; Accepted 13 November 2001mentioning
confidence: 99%
“…Indeed, entire symposia have been organized on the premise of massive declines in Neotropical migratory birds (Finch andStangel 1992, Hagan andJohnston 1992). But as the supposed declines have been examined in more detail, the picture doesn't seem nearly as clear as it should be.…”
Section: Special Featurementioning
confidence: 99%
“…Partners in Flight, the multi-agency coalition responsible for initiating the Neotropical Migratory Bird Conservation Program (Finch and Stangel 1993), has suggested that continental monitoring programs such as the BBS should be able to detect a 50% decline in the population of a species over 25 yr with 90% power (Butcher et al 1993). The purpose of the simulation study described here was to evaluate the bias and efficiency of three BBS trend-estimation methods in the context of linear-multiplicative declines of this magnitude and under three different geographic scenarios of population change.…”
Section: Simulationsmentioning
confidence: 99%